Current research in Egyptology 2018 : proceedings of the Nineteenth Annual Symposium, Czech Institute of Egyptology, Faculty of Arts, Charles University, Prague, 25-28 June 2018 - Hlouchova, Marie Peterkova,; Belohoubkova, Dana,; Honzl, Jirí,; Novakova, Vera, (Archaeopress, 2019)
Current Research in Egyptology 2018' is a collection of papers and posters presented at the nineteenth symposium of the prestigious international student conference, held at the Faculty of Arts, Charles University in Prague on 25th-28th June 2018. The Prague conference was attended by more than 100 people from various countries and institutions. The range of topics discussed was wide, covering all periods of ancient Egyptian and Nubian history and various topics concerning their society, religious life, material culture and archaeological excavations. The event also included six keynote lectures by experts from the Czech Institute of Egyptology, the FA CU (Prof. Mgr. Miroslav Barta, Dr., Doc. PhDr. Hana Vymazalova, Ph.D., Doc. PhDr. Jana Mynarova, Ph.D., Prof. PhDr. Ladislav Bares, CSc., and PhDr. Filip Coppens, Ph.D.) and the University of Vienna (Ao. Univ.-Prof. Dr. Peter-Christian Janosi). The Egyptological meeting was enriched with a visit to the Karolinum, historical buildings of Charles University.